A framework and risk analysis for supply chain emission trading - Fang Li; Lydia Schwarz; Hans-Dietrich Haasis (Logistics Research, 2016)
Reports show that it is necessary to control greenhouse gas emissions from the supply chain perspective. Numerous authors have already started quantifying the impacts of emission trading on supply chain performance in terms of cost and emissions. However, rare effort is made to conceptualize this implementation. This paper generates firstly one conceptual framework for supply chain emission trading through a review of previous work and then asserts how practically it could work out. In addition, the risks confronted by firms and supply chains under emission trading are identified considering each step involved in the framework. These risks are further classified based on the concept of supply chain risks. Results show that the implementation of emission trading on supply chain would raise additional risks into existing supply chain risk portfolio. At last, this paper provides some risk mitigation measures for those identified risks.
Keywords: 650; Emission trading; Supply chain greenhouse gas emissions; Risk analysis; Supply chain emission trading